2010
DOI: 10.1016/j.jpor.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of new self-adhesive resin-based cement

Abstract: It is suggested that the new self-adhesive resin cements exhibited a favorable bonding capability and mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 17 publications
4
88
0
7
Order By: Relevance
“…This finding is in accordance to the results of other studies [20,30]. Water absorption of different self-adhesive resin cements varies [31]. In a recent study, GCM showed significantly higher water absorption than PAN, RXU or CSA [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in accordance to the results of other studies [20,30]. Water absorption of different self-adhesive resin cements varies [31]. In a recent study, GCM showed significantly higher water absorption than PAN, RXU or CSA [31].…”
Section: Discussionsupporting
confidence: 92%
“…Water absorption of different self-adhesive resin cements varies [31]. In a recent study, GCM showed significantly higher water absorption than PAN, RXU or CSA [31]. While absorption of water results in an expansion of the material, the anchorage of the cement in the acid etched ceramic roughness is expected to be higher.…”
Section: Discussionmentioning
confidence: 98%
“…00609), and the embedding molds were filled with autopolymerizing acrylic resin to the upper rim. The screw-hole of the lower embedding mold was then removed, and the teeth were positioned in a custom-made device with a preparation angle of 10 degrees and prepared with a diamond rotary instrument (16 Torpedo; Komet Dental) in a parallelometer (F4-basic; DeguDent GmbH) with water-cooling.…”
Section: Methodsmentioning
confidence: 99%
“…6 Thermocycling is an appropriate method for the in vitro aging of specimens to test bonding properties, as the stress for all specimens is standardized and reproducible. [12][13][14][15][16][17] Many studies have tested the bond strength immediately after specimen fabrication or after 24 hour water storage, 4,5,8 which only leads to a limited amount of information. Studies so far have only investigated geometric specimens.…”
Section: Introductionmentioning
confidence: 99%
“…SA exhibited superior bonding durability, with no statistically significant difference in SBS before and after thermocycling and yielding the highest SBS among all the cements after thermocycling. Two reasons probably accounted for this result: inclusion of adhesive monomer MDP and an improved polymerization initiation system 22) . It has been reported that the MDP monomer demonstrated excellent bonding to non-precious alloys [23][24][25] .…”
Section: Discussionmentioning
confidence: 94%